Emotional Exhaustion in Ministry as Predictor of Sexual Attitudes of Nigerian Christian Clergy - , Promisen E. Nwaka; , Olutope E. Akinnawo; , Alfred Awaritefe; , Bede C. Akpunne (Archives of Current Research International, 2020)
The study aimed to examine Emotional Exhaustion (EE) of the minister as predictor of the Christian clergy sexual attitudes in an era of “#ChurchToo” crusade and sexual crisis facing the church globally yet, there are not sufficient empirical data on the Christian clergy regarding dynamics that are responsible for permissive sexual attitudes and behaviours. Five hundred and sixty-two (562) Christian clergy (410 male, 152 female), mean age 34.7± 0.1 were purposively selected from Protestant, Pentecostal and White garment churches in south-western Nigeria who responded to Emotional Exhaustion in Ministry (SEEM) and Brief Sexual Attitudes Scale (BSAS). Descriptive and inferential statistics were used for data analyses. The observed prevalence of high burnout was 14.0%. Emotional exhaustion in ministry significantly predicted Birth control (sexual responsibility) Birth control (sexual responsibility) (Sexual responsibility) attitude, communion attitude, instrumentality attitude and permissiveness attitude. There were statistically significant sex differences in the mean (± SD) scores of Birth control (sexual responsibility) attitude, Communion attitude and permissiveness attitude. Male and female clergy had similar mean (± SD) score on instrumentality. Findings demonstrate that emotional exhaustion in ministry is strongly linked with several dimensions of sexual attitudes in unique ways, and that gender deference in sexual attitude exists among the clerics.